Shang-Ke-Huang-Shui and coptisine alleviate osteoarthritis in the knee of monosodium iodoacetate-induced rats through inhibiting CXCR4 signaling. (15th July 2023) - Yang, Kuangyang; Xie, Qian; Liao, Jiaxin; Zhao, Na; Liang, Jianhui; Liu, Ben; Chen, Jianhai; Cheng, Wenxiang; Bai, Xueling; Zhang, Peng; Liu, Qian; Song, Bing; et al.
Abstract: Ethnopharmacological relevance: Shang-Ke-Huang-Shui (SKHS) is a classic traditional Chinese medicine formula originally from the southern China city of Foshan. It has been widely used in the treatment of osteoarthritis (OA) but underlying molecular mechanisms remain unclear. Aim of study: Recently, activation of C-X-C chemokine receptor type 4 (CXCR4) signaling has been reported to induce cartilage degradation in OA patients; therefore, inhibition of CXCR4 signaling has becoming a promising approach for OA treatment. The aim of this study was to validate the cartilage protective effect of SKHS and test whether the anti-OA effects of SKHS depend on its inhibition on CXCR4 signaling. Additionally, CXCR4 antagonist in SKHS should be identified and its anti-OA activity should also be tested in vitro and in vivo . Methods: The anti-OA effects of SKHS and the newly identified CXCR4 antagonist was evaluated by monosodium iodoacetate (MIA)-induced rats. The articular cartilage surface was examined by hematoxylin and eosin (H&E) staining and Safranin O-Fast Green (S–F) staining whereas the subchondral bone was examined by micro-CT. CXCR4 antagonist screenings were conducted by molecular docking and calcium response assay. The CXCR4 antagonist was characterized by UPLC/MS/MS. The bulk RNA-Seq was conducted to identify CXCR4-mediated signaling pathway. The expression of ADAMTS4, 5 was tested by qPCR and Western blot. Results: SKHS protected rats from MIA-induced cartilage degradation and subchondral bone damage. SKHS also inhibited CXCL12-indcued ADAMTS4, 5 overexpression in chondrocytes through inhibiting Akt pathway. Coptisine has been identified as the most potent CXCR4 antagonist in SKHS. Coptisine reduced CXCL12-induced ADAMTS4, 5 overexpression in chondrocytes. Furthermore, in MIA-induced OA model, the repaired cartilage and subchondral bone were observed in the coptisine-treated rats. Conclusion: We first report here that the traditional Chinese medicine formula SKHS and its predominate phytochemical coptisine significantly alleviated cartilage degradation as well as subchondral bone damage through inhibiting CXCR4-mediated ADAMTS4, 5 overexpression. Together, our work has provided an important insight of the molecular mechanism of SKHS and coptisine for their treatment of OA. Graphical abstract: Image 1 Highlights: Shang-Ke-Huang-Shui (SKHS), a traditional Chinese medicine formula, protects rats from MIA-induced cartilage degradation. Coptisine has been identified as the most potent CXCR4 antagonist in SKHS. Coptisine inhibits ADAMTS4, 5 overexpression in chondrocytes through inhibiting Akt signaling pathway. Coptisine alleviates symptoms of OA and reduces ADAMTS4, 5 expression in MIA-induced rats.